2012
DOI: 10.1002/ange.201106334
|View full text |Cite
|
Sign up to set email alerts
|

Duocarmycin Analogues Target Aldehyde Dehydrogenase 1 in Lung Cancer Cells

Abstract: Neue Ziele: Mithilfe von Proteomikstudien wurde nachgewiesen, dass Aldehyd‐Dehydrogenase 1 eine zusätzliche oder alternative Zielverbindung von Duocarmycin sein könnte. Selektive Inhibierung dieses Enzyms in Lungenkrebszellen erklärt die Antitumoraktivität von Duocarmycinanaloga (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 33 publications
0
23
0
7
Order By: Relevance
“…However, Wirth et al. demonstrated that the pulldown probe of the natural product duocarmycin SA (Table 1, entry 1) only isolates a second target protein (aldehyde dehydrogenase, ALDH1A1) for the natural product after incubation with living cells, as opposed to treatment with cell lysates which emphasizes that lysis condition might compromise binding of the target protein to the ligand 28…”
Section: Approaches To Target Identificationmentioning
confidence: 99%
“…However, Wirth et al. demonstrated that the pulldown probe of the natural product duocarmycin SA (Table 1, entry 1) only isolates a second target protein (aldehyde dehydrogenase, ALDH1A1) for the natural product after incubation with living cells, as opposed to treatment with cell lysates which emphasizes that lysis condition might compromise binding of the target protein to the ligand 28…”
Section: Approaches To Target Identificationmentioning
confidence: 99%
“…With the advances of mass spectrometry (MS) technologies, it is feasible to further identify the specific probe-labelling sites on protein targets. For example, the probe is directly incubated with purified proteins identified with ABPP and then labelled proteins are digested and desired peptides are analyzed by MS/MS11. Another promising method for binding site mapping performed in live cells is gel-free ABPP to identify probe-labelled peptides, including the selective enrichment and elution of probe-labelled peptide fragments121314.…”
mentioning
confidence: 99%
“…Duocarmycins are known to bind and alkylate DNA in AT-rich regions of the minor groove, and induce cell death in a way dependent of DNA replication (Boger et al 1994;Tietze et al 2006;Tietze et al 2009) We checked that senescent cells were growth arrested at the time of the drug treatment (Sup Fig 1). This shows that the effect observed is not due to hyperreplication of cells during early stages of OIS and suggest that the prodrug might act by some of the alternative cytotoxic mechanisms described for duocarmycin dimers (Wirth et al 2012). Treatment with prodrug A induced caspase 3/7 activity on senescent cells (Fig 1c), and the selective death of this cells was prevented with a pan-caspase inhibitor (Fig 1d).…”
Section: A Galactose-modified Duocarmycin Prodrug With Senolytic Propmentioning
confidence: 73%
“…Duocarmycins are a group of antineoplastic agents with low picomolar potency. They are thought to act by binding and alkylating double stranded DNA in AT-rich regions of the minor groove, (Boger et al 1994;Tietze et al 2006;Tietze et al 2009), but alternative mechanisms of action have been proposed to account for the cytotoxic effects of duocarmycin dimers (Wirth et al 2012).…”
Section: Introductionmentioning
confidence: 99%